ANALISIS PEMBERIAN TUNJANGAN DAN BONUS DALAM MENINGKATKAN LOYALITAS KARYAWAN PADA PT. TELKOM CABANG SUMBAWA - R Fitriani; S Suprianto (Samalewa: Jurnal Riset & Kajian Manajemen, 2023)
This study aims to know the effect of allowances giving and bonuses on employees loyalty at PT. Telkom Branch of Sumbawa. The type of this study was associative study. The types of data used were quantitative and qualitative data. Sources of data in this study were primary and secondary data. Total populations were 80 respondents. The technique of determining sample used was saturated sample (cencus sampling.  Thus the sample in this study amounted to 44 people. The methods used to collect data were questionnaire and documentation. The data analysis technique used were the Classical Assumption Test, multiple linear regression analysis, t-test, F test and R2 test through SPSS software version 16.0 for windows. The results showed that partially the provision of benefits did not have a significant effect on employee loyalty, while bonuses had a positive and significant effect on employee loyalty at PT. Telkom branch of Sumbawa. Simultaneously the provision of allowances and bonuses has a significant effect on employee loyalty at PT. Telkom branch of Sumbawa. The percentage of influence of allowances and bonuses on employee loyalty at PT. Telkom branch of Sumbawa is 55.2%, while the remaining 44.8% is influenced by other variables outside of this study, such as leadership style, work stress, compensation, and work environment.